Dimensões da aula e das práticas pedagógicas na educação superior presencial e a distância - Arruda, Durcelina Ereni Pimenta (2011)
The thesis presented here was developed with the participation of five teachers (as) who work in the Faculty of Education Faculty of Education classroom course and distance Education, Federal University of Uberlandia in Minas Gerais. The research objectives are: 1) Identify and analyze the relationships established between university professors teaching practices in distance education and its relationship with the consolidated practices of these teachers face in education, and 2) Understanding the interrelationships between teaching practices in different forms of education, in order to analyze the possible actions of the changes and continuities in teacher education and distance education classroom. This research was based on the analysis proposed by exploratory qualitative research and the data were constructed using a questionnaire and semi-structured questionnaire with open and closed questions. During the construction of the text sought to make considerations about the Teaching in Higher Education: distances and presences in the constitution of the university teacher's work and on distance education in higher education in Brazil: historical aspects and current conditions. Another great aspect of relevance addressed in the text it comes to training teachers to work with technology and distance education and skills in making didactic and pedagogical work with both types of education.